2002
DOI: 10.1017/s0047404502315033
|View full text |Cite
|
Sign up to set email alerts
|

Growing up monolingual in a bilingual community: The Quichua revitalization paradox

Abstract: A B S T R A C TThe present investigation concerns language ideology and language practices in relation to a language shift -from Quichua-Spanish bilingualism to Spanish monolingualism -that seems to be under way. The analyses are based on fieldwork in an Ecuadorian sierra community characterized by ethnic revitalization. Among adult comuneros, the vernacular is seen as an essential part of their Indian cultural heritage. In the children's daily lives, the adults, particularly women and the elderly, speak Quich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 24 publications
2
36
0
11
Order By: Relevance
“…However, socialization is not a static top-down process of intergenerational transmission of knowledge: rather, as recently emphasized by this research paradigm, it is dynamic and dialectic (Duranti et al 2012;Cekaite 2012). Children themselves contribute to the process of forming the language policy around them, and their willing participation in adult-initiated practices cannot be assumed (Paugh 2005;Rindstedt and Aronsson 2002). Current sociolinguistic perspectives foreground the multi-scalar character of linguistic and interactional resources (Blommaert, 2010).…”
Section: Language Maintenance In a Multilingual Family: Informal Herimentioning
confidence: 98%
See 1 more Smart Citation
“…However, socialization is not a static top-down process of intergenerational transmission of knowledge: rather, as recently emphasized by this research paradigm, it is dynamic and dialectic (Duranti et al 2012;Cekaite 2012). Children themselves contribute to the process of forming the language policy around them, and their willing participation in adult-initiated practices cannot be assumed (Paugh 2005;Rindstedt and Aronsson 2002). Current sociolinguistic perspectives foreground the multi-scalar character of linguistic and interactional resources (Blommaert, 2010).…”
Section: Language Maintenance In a Multilingual Family: Informal Herimentioning
confidence: 98%
“…Studies adopting a dynamic perspective on language socialization have demonstrated that children's language choices and interactional practices significantly influence and shape parental language behavior (Luykx 2005;Gafaranga 2010), and that children actively contribute to language maintenance (Paugh 2005) Children's participation in educational practices in the majority language, together with their siblings and peers, constitutes a strong language socializing factor that contributes to generational language shift (Rindstedt and Aronsson 2002;Evaldsson and Cekaite 2010).…”
Section: Children's Participation In Heritage Language Practicesmentioning
confidence: 99%
“…Particularly language socialization studies on children's peer interactions in noninstitutional bilingual settings (i.e., at home and in the neighbourhood) have shown that children's peer interactions provide an important context for linguistic and cultural socialization (Paugh 2005; see also Garrett 2000;Kulick 1992;Rindstedt & Aronsson 2002). For example, Rindstedt and Aronsson (2002) have shown that despite adults' efforts to instill children's learning and use of Quichua, sibling interactions in Spanish provided a powerful factor that contributed to the children's monolingualism.…”
Section: Children's Peer Group Interactions As a Language Socializatimentioning
confidence: 99%
“…For instance, siblings can have constraining effects on minority language learning and as a result contribute to language shift. Rindstedt and Aronsson's (2002) language socialization study of intergenerational language practices in a Quichua-Spanish community showed that sibling play is a significant site for home language transmission. Siblings' language choices during caretaking and play, and in adult-child interactions (children's interactions with grandparents and parents) revealed the process of language shift underway.…”
Section: Siblings and Family Language Practicesmentioning
confidence: 99%
“…Here, socialization is conceptualized not as a static top-down process of intergenerational transmission of knowledge, but rather as dynamic and dialectic (Cekaite 2012;Duranti et al 2012). Accordingly, children themselves contribute to the process of forming the language policy around them, and their willing participation in adult-initiated practices cannot be assumed (Paugh 2005;Rindstedt and Aronsson 2002).…”
Section: Implications For Future Researchmentioning
confidence: 99%